Analysis of Work-Family Conflict and its Influence on Turnover Intention of Civil Servant Teachers at Bogor Regency Education Office - Prasetyo, Ananto; Irawati, R Ira; Rusliandy, Rusliandy (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
Imbalance in the number of teachers has led to the emergence of new teacher turnover proposals. This contradicts the mutation policy outlined in Minister of Administrative and Bureaucratic Reform Regulation (Permenpan RB) Number 36 of 2018 and Number 23 of 2019 regarding the Criteria for Determining Civil Servant Needs and the Implementation of Civil Servant Candidate Selection. The trend of proposals for civil servant teacher turnover has shown an increasing tendency over the past 3 years, particularly from 2020 to 2022. This study aimed to identify and analyze the impact of family conflicts on the turnover intention of civil servant teachers. The research methodology employed a mixed-method approach (MMR), combining qualitative and quantitative analyses. Primary data collection involved distributing questionnaires to 394 teacher respondents, conducting interviews with experts, and employing Structural Equation Model (SEM) PLS for data analysis. The research findings indicated that Work-Family Conflicts significantly influenced the turnover intention of civil servant teachers, with a path coefficient of 0.506, a p-value of (0.000 < 0.005), and a t-value of (12.830 > 1.96). Recommendations that could be implemented by the Bogor District Education Office to reduce the number of proposals for civil servant teacher turnover include policies aligning civil servant placements with residential zones, conducting a comprehensive analysis of school-specific teacher requirements, fostering commitment and support from school leadership, and implementing sanctions and incentives (such as providing scholarships) as outlined in the PermenpanRB.